Novel molybdenum disulfide nanosheets–decorated polyaniline: Preparation, characterization and enhanced electrocatalytic activity for hydrogen evolution reaction. (April 2016) - Ding, Shuangshuang; He, Ping; Feng, Wanru; Li, Lian; Zhang, Guangli; Chen, Jingchao; Dong, Faqin; He, Huichao
Abstract: Novel molybdenum disulfide nanosheets–decorated polyaniline (MoS2 /PANI) was synthesized and investigated as an efficient catalyst for hydrogen evolution reaction (HER). Compared with MoS2, MoS2 /PANI nanocomposites exhibited higher catalytic activity and lower Tafel slope for HER in H2 SO4 solution. The amount of 19 wt% PANI for coupling with MoS2 resulted in a high current density of 80 mA cm −2 at 400 mV (vs. RHE). In addition, the optimal MoS2 /PANI nanocomposite showed impressive long-term stability even after 500 cycles. The enhanced catalytic activity of MoS2 /PANI nanocomposites was primarily ascribed to the effective electron transport channels of PANI and the increase of electrochemically accessible surface area in composite materials, which was advantageous to facilitate the charge transfer at catalyst/electrolyte interface. Graphical abstract: Shown in left was the morphology of MoS2 /PANI-5 sample. As we can see, MoS2 nanosheets were homogeneously dispersed on the surface of PANI and tended to exist in the form of smaller nanosheets. Shown in right were the steady-state polarization curves of MoS2 /PANI-3, MoS2 /PANI-4, MoS2 /PANI-5, MoS2 /PANI-7 and Pt electrodes in 0.50 M H2 SO4 solution at 293 K. It was observed that MoS2 /PANI-5 electrode presented the optimized cathodic current density at the same potential. Highlights: Novel MoS2 nanosheets–decorated PANI was synthesized. Aggregation of MoS2 nanosheets were prevented by homogeneously distributing on PANI. PANI was used as conductive substrate to promote electron transport of composite. The composite exhibited higher electrocatalytic activity for HER than pure MoS2 . The composite with 19 wt% PANI showed current density of 80 mA cm −2 at 400 mV.